Prevalence and Associated Factors of Work-Related Spinal Pain Among Bank Workers in Harar, Eastern Ethiopia: A Cross-Sectional Study - Murad Umer MPH; Aboma Motuma PhD; Nesredin Ahmed MSc; Shiferaw Letta PhD (SAGE Open Nursing)
Background Spinal pain is a prevalent occupational health issue, particularly among bank workers who often experience prolonged sitting and poor ergonomic conditions. Despite the increasing occupational-related burden of spinal pain, data specific to bank workers in study setting, remains limited. Objective This study aimed to determine the prevalence of spinal pain and its associated factors among bank workers in Harar, Eastern Ethiopia. Methods An institution-based cross-sectional study was conducted among 322 bank workers from July 20 to August 20, 2023. Participants were selected using a simple random sampling technique to ensure unbiased representation. The standardized Nordic Musculoskeletal survey was interviewer-administered for data collection. Data were entered in EpiData version 3.1 and exported to STATA version 17.0 for analysis. Descriptive statistics, including frequencies and percentages, were applied to calculate the proportion. Bivariate and multivariable binary logistic regression was conducted to identify factors associated with spinal pain, with an alpha level of 0.05 defining statistical significance. Adjusted odds ratios with their 95% confidence intervals were used to assess the strength and direction of associations. Results The study found that lower back pain (45.4%), neck pain (37.14%), and upper back pain (34.92%) were the most frequently reported spinal complaints among bank employees in the past 12 months. Neck pain was associated with female gender, job stress, and high workload. Lower back pain showed association with alcohol consumption, longer duration of service, managerial roles, and workload intensity. Upper back pain was associated with being in a managerial position. Conclusion The study highlights a high burden of spinal pain among bank workers, with distinct associations across neck, upper back, and lower back regions. Ergonomic strain, occupational stress, behaviors, and job roles significantly contributed to pain. These findings underscore the need for targeted workplace interventions that address both physical and psychosocial risk factors to enhance employee wellbeing in banking environments.